Caulobacter flagellar organelle: synthesis, compartmentation, and assembly. - Lagenaur, C (1978)
In Caulobacter crescentus biogenesis of the flagellar organelle occurs during one stage of its complex life cycle. Thus in synchronous cultures it is possible to assay the sequential synthesis and assembly of the flagellum and hook in vivo with a combination of biochemical and radioimmunological techniques. The periodicity of synthesis and the subcellular compartmentation of the basal hook and filament subunits were determined by radioimmune assay procedures. Unassembled 27,000-dalton (27K) flagellin was preferentially located in isolated membrane fractions, whereas the 25K flagellin was distributed between the membrane and cytoplasm. The synthesis of hook began before that of flagellin, although appreciable overlap of the two processes occurred. Initiation of filament assembly coincided with the association of newly synthesized hook and flagellin subunits. Caulobacter flagella are unusual in that they contain two different flagellin subunits. Data are presented which suggest that the ratio of the two flagellin subunits changes along the length of the filament. Only the newly synthesized 25K flagellin subunit is detected in filaments assembled during the swarmer cell stage. By monitoring the appearance of flagellar hooks in the culture medium, the time at which flagella are released was determined.